До питання про другого сина Володимира Мономаха та час його народження - Васюта, О. (Сiверянський лiтопис, 2019)
Як видно з літописів Київської Русі, для їхніх авторів політична постать Володимира Мономаха була дуже авторитетною. Однак його родинному життю вони приділили обмаль уваги. Через це ієрархія старшинства Мономаховичів усе ще залишається до кінця нез’ясованою. У даній статті автор визначає час народження Ізяслава Володимировича, який засвідчує, що він був саме другим сином Володимира Мономаха. At the Middle Ages, the authors of historical works, according to the tradition of their era, always paid the most attention exactly for the representatives of the ruling elites who occupied the highest places in the social hierarchy of the contemporary society. Accordingly, the pages of medieval European chronicles abound names of «strong» world of that. In the last, there are also frequent reports of their genealogy, dynastic relationships, years of birth and death. For researchers, this information is of great importance, because thanks to that are acquired much broader also for the interpretation of other events. In this plan, the chronicles of Kievan Rus did not become an exception, which provides a lot of information about the representatives of the local ruling princely family of Rurykovych. As can be seen from these historical sources, for their authors, the political figure of Volodymyr Monomakh was very authoritative, but, alas, they paid little attention to this family life. Because of this, the hierarchy of the seniority of his sons is still unclear. In the sources among the latter, the first one mentions Mstyslav (1076), then Svyatoslav (1095), Izyaslav (1095), Vyacheslav (1096), Andriy (1102), Yaropolk (1103), Yuriy (1108) and Roman (1113). However, the birth years are recorded only to Mstyslav and Andrei Volodymyrovych. The generally accepted thesis is that they were also, respectively, the eldest and youngest sons of Monomakh. Some cursory chronicle testimonies also point out that Svyatoslav, Izyaslav, Vyacheslav, and Yaropolk also belonged to the elder sons of Volodymyr Vsevolodovych. Moreover, Yaropolk and Vyacheslav were younger than Svyatoslav, and Vyacheslav at the age yielded to Yaropolk. As for Izyaslav Volodymyrovych place in the hierarchy among the sons of Monomakh sources do not provide specifics. For today among historians concerning Izyaslav Volodymyrovych’s time of birth there are two points of view. V. A. Kuchkin considers that this happened until April 10, 1078, and A. F. Lytvyn with F. B. Uspenskyi – after October 3, 1078. Both versions based on the analysis of political events and the mention in the letter of Volodymyr Monomakh to Oleg Svyatoslavych about the god-fatherhood of the last relative to Izyaslav Volodymyrovych. However, a thorough analysis of the events of 1077-1078 made in this article, in conjunction with the information of the letter Monomakh, as it turns out, does not allow to agree with the conclusions of the named researchers and indicates that Izyaslav Volodymyrovych was born until May 4, 1077. According to the author, this happened in the winter of 1077. In the author’s opinion, it happened in the winter of 1077. Accordingly, this definition of Izyaslav Volodymyrovych’s birth-time also puts a point on his seniority among the Monomakhovychs, testifying that by age he was the second son of Volodymyr Monomakh.